Posterior Instrumentation without Curettage Promotes Rapid Restoration of Adult Spinal Langerhans Cell Histiocytosis - Bungo Otsuki; Hiroaki Kimura; Shunsuke Fujibayashi; Takayoshi Shimizu; Takashi Sono; Koichi Murata; Shuichi Matsuda (Spine Surgery and Related Research)
Introduction: Adult spinal Langerhans cell histiocytosis (LCH) presents a treatment challenge due to ongoing controversies. Traditional approaches such as curettage with bone grafting and internal fixation are preferred for severe cases involving mechanical instability, neurological deficits, or deformity. This study aimed to explore the efficacy of a customized approach involving simple posterior instrumentation without curettage or bone grafting in treating adult spinal LCH. Methods: This retrospective study analyzed a prospectively maintained database of all spine surgeries conducted at our institute from April 2013 to December 2020. Adult patients (age20) diagnosed with LCH were included. We assessed surgical methods, adjuvant therapy, and clinical results, such as perioperative progression of disease, symptoms, and recurrence. Results: Four male patients aged between 21 and 28, each with a single spinal LCH lesion (T6, T5, and C5) except one case (T5 and T7), were treated. Diagnoses were confirmed via biopsy (two open, two needle biopsies). Whole-body computed tomography or bone scintigraphy revealed no additional LCH lesions in any patient, except in one patient with a small lung nodule. All patients presented with severe back or neck pain and pathological fractures at the affected vertebra. Thoracic LCH cases received percutaneous pedicle screw fixation, while the cervical case was managed with conventional posterior instrumentation using lateral mass screws. After surgery, all patients experienced significant pain relief, halted bone lysis, and rapid new bone formation. One patient underwent chemotherapy postsurgery. Over 3 years of follow-up, imaging studies revealed no recurrences of the disease. Conclusions: Posterior instrumentation, without the need for curettage or bone grafting, is a promising surgical treatment for adult spinal LCH. This method may effectively halt lesion progression, prevent spinal deformity, and avert neurological deficits in the patients with progressive spine lesion where conservative treatment may not adequately prevent vertebral fractures.